2015
DOI: 10.1039/c5an01112d
|View full text |Cite
|
Sign up to set email alerts
|

A novel substitution -sensing for hydroquinone and catechol based on a poly(3-aminophenylboronic acid)/MWCNTs modified electrode

Abstract: A facile electrochemical sensor for hydroquinone (HQ) and catechol (CC) determination was successfully fabricated by the modification of poly(3-aminophenylboronic acid) (pAPBA) film and multi-walled carbon nanotubes (MWCNTs) on a glassy carbon electrode (pAPBA/MWCNTs/GCE). The prepared sensor was characterized by scanning electron microscope and electrochemical impedance spectroscopy. Under optimal conditions, differential pulse voltammetry was employed to quantify individual HQ and CC within the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The detection limit (LOD) of catechol was determined to be 6.2 nmol/L (S/N=3), while the LODs of most of electrochemical detectors in a conventional flow‐injection system are on the sub‐μmol/L level . In addition, this LOD for catechol was comparable or superior to those of microfluidic analytical systems with electrochemical detection (Table S1) . The present study confirmed the high sensitivity and good performance of the developed flow cell with the optimized ring array electrode.…”
Section: Resultssupporting
confidence: 69%
“…The detection limit (LOD) of catechol was determined to be 6.2 nmol/L (S/N=3), while the LODs of most of electrochemical detectors in a conventional flow‐injection system are on the sub‐μmol/L level . In addition, this LOD for catechol was comparable or superior to those of microfluidic analytical systems with electrochemical detection (Table S1) . The present study confirmed the high sensitivity and good performance of the developed flow cell with the optimized ring array electrode.…”
Section: Resultssupporting
confidence: 69%
“…The resistance of the charge transfer on the electrode surface (R ct ) is represented as a semicircle diameter in the Nyquist diagram. The bare GCE presented a semicircle (∼251.1 Ω) domain as expected for a very low electron transfer resistance to the redox probe (Figure A).…”
Section: Resultsmentioning
confidence: 76%
“…Also, E pa shifted to more positive values with the increased in the scan rates, proposing the electron transfer be quasi‐reversible .…”
Section: Resultsmentioning
confidence: 99%
“…It is important to indicate that, to date, electrochemical methods [1, 29–43], have been applied to the detection of catechol. For this reason, a comparison of the proposed method with other electrochemical methods by using modified materials was listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%